Finite-time stabilization of input-delay switched systems - Lin, Xiangze; Zhang, Wanli; Huang, Shuaiting; Zheng, Enlai (Applied mathematics and computation, 2020)
In the framework of digital control, finite-time stabilization of input-delay switched systems with saturating actuators is investigated. Digital state feedback controllers (DSFC) and digital output feedback controllers (DOFC) are proposed to make input-delay switched systems finite-time stable for the cases that states are available or unavailable. Sufficient conditions for finite-time stability (FTS) of the resultant closed-loop systems are also presented. A constructive way is used to proof the main results, which is constructing an exact comparison function. Numerical examples are employed to verify the efficiency of the methods proposed in this paper.